Implementation of Data Mining to predict sales of Bogo helmets using the Naïve Bayes algorithm - Mariskhana, Kartika; Sintawati, Ita Dewi; Widiarina, Widiarina (Politeknik Ganesha Medan, 2022)
Consumer needs for safety and comfort in driving are very important, especially for two-wheeled or motorcycle riders. A good helmet is a helmet that is safe and comfortable when worn. Helmet qualifications that meet SNI standards are open helmets and closed helmets. Transactions are carried out online, because it was still in a pandemic situation when it was established. By carrying the tag line